2020
DOI: 10.1097/jtn.0000000000000540
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to the Implementation of Injury Prevention Programs: A Qualitative Exploration and Model Development

Abstract: Background: In 2006, the American College of Surgeons Committee on Trauma mandated implementation of injury prevention programs as a requirement for Level I and II trauma center designation. Little is known about the factors that facilitate or create barriers to establishing evidence-based injury prevention program implementation. The purpose of this research is to generate hypotheses regarding processes used to implement injury prevention programs at trauma centers, identify the factors that facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The injury prevention coordinators’ work was influenced by the support from direct managers and senior leadership 26 …”
Section: Resultsmentioning
confidence: 99%
“…The injury prevention coordinators’ work was influenced by the support from direct managers and senior leadership 26 …”
Section: Resultsmentioning
confidence: 99%
“…In a qualitative study of hospital-based injury prevention programs identifying factors that facilitate or serve as barriers to implementing evidence-based prevention programs, the analysis revealed that successful implementation was related to supportive institutional leadership and collaborative interdepartmental relationships; however, study participants indicated these factors were not the norm. Instead, limited training opportunities for staff orientation, professional development, funding availability, and program selection hindered program capacity ( Newcomb et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A trauma training clinician survey emphasised developing interpersonal staff communication alongside strengthening emergency communication methods [30]. Limited staff knowledge acts as a hurdle to improved communication [9,22,23,31]. A subject from a US injury prevention program highlighted the lack of healthy understanding of QI requirements as they are viewed as "the black sheep" of the department, making it a constant struggle to "seek out other mentors of people that do similar work" [31 p.339].…”
Section: Domain 4: Characteristics Of Individualsmentioning
confidence: 99%
“…Identifying staff to as a champion for the QI intervention is signi cant [17,31,33,39]. Trauma registry questionnaire respondents felt that limited stakeholder engagement could be overcome by having a champion to drive and mobilise buy-in [33].…”
Section: Domain 5: Process Of Implementationmentioning
confidence: 99%
See 1 more Smart Citation